The difference between artificial intelligence implicatures and human implicatures in conversation - Raghad Hawarin; Dr. Mahmod Eshreateh (Yayasan Mitra Persada Nusantara, 2026)
This research investigates the pragmatic differences between conversational implicatures produced by artificial intelligence systems and those generated by humans in everyday conversation. Grounded in Grice’s Cooperative Principle and its four conversational maxims—quantity, quality, relation, and manner—the study analyzes how implicatures emerge, function, and are interpreted in human–human and human–AI